She speaks : the power of women's voices - Cooper, Yvette (London : Atlantic Books, 2019)
Looking at the greatest speeches of all time, you'd be forgiven for thinking that Elizabeth I and Boudica were about the only women to have dipped a toe into the pool of public oratory. But the truth is very different - countless brave and bold women have used their voices to inspire change, transform lives and radically alter history. In this timely and personal anthology, Yvette Cooper MP tells the story of 30 inspirational speeches given by women. From Boudica to Margaret Thatcher and from Malala to gun-control activist Emma Gonzalez, each speech will be reproduced in full and introduced by Yvette. This is not only a much-needed celebration of women's speeches throughout history, but also proof that powerful and persuasive oratory can be decidedly female.
A woman's resolve / Boudica -- The heart and stomach of a king / Queen Elizabeth I -- I am a woman's rights / Sojournor Truth -- A voice in the wilderness / Josephine Butler -- Freedom or death / Emmeline Pankhurst -- An insult to mothers / Eleanor Rathbone -- The promise of a dream / Joan O'Connell -- There are so many silences to be broken / Audre Lorde -- The lady's not for turning / Margaret Thatcher -- On the pulse of morning / Maya Angelou -- The ethos of Islam in equality between the sexes / Benazir Bhutto -- The red light has gone on / Barbara Castle -- A message of hope and healing / Eva Kor -- Modernising the conservative party / Theresa May -- A world of beauty and wonder / Wangari Maathai -- I know who I am / Ellen Degeneres -- A door suddenly opened / Angela Merkel -- Get up there and get at it / Alison Drake -- No limbs no limits / Joanne O'Riordan -- He needs a mirror / Julia Gillard -- We should all be feminists / Chimamanda Ngozi Adichie -- Let us pick up our books and our pens / Malala Yousafzai -- Freedom without fear / Kavita Krishnan -- Being beautiful inside / Lupita Nyong'O -- Parliament must lead by example / Harriet Harman -- HeForShe / Emma Watson -- More in common / Jo Cox -- Britain has to play our part / Yvette Cooper -- When they go low, we go high / Michelle Obama -- Physics is fun / Donna Stickland -- Today I rise / Alexandria Ocasio-Cortez -- They are us / Jacinda Ardern -- We will not rest / Diane Abbott -- We are making history today / Lilit Martirosyan -- Let's start acting / Greta Thunberg.
Includes bibliographical references.
Keywords: Speeches, addresses, etc; Public speaking for women; Women -- Social conditions; Women -- Political activity